A decomposition and decoupling analysis for carbon dioxide emissions: evidence from OECD countries - Mohammad Abedin (Environment, Development and Sustainability, 2024)
Despite the huge difference in their climatic regimes, the OECD countries are among the world’s largest energy consumers and emitters of greenhouse gases, particularly carbon dioxide. Nonetheless, no studies have been conducted to decompose and decouple the long-term influential primary factors of carbon emissions for these countries. In this research, the Log Mean Divisia Method I is used to inspect the contribution of several influencing factors to fill this knowledge gap. Moreover, Tapio (Transp Policy 12(2):137–151, 2005) decomposition analysis (DA) is performed to investigate the driving forces of CO2 emissions over the 1990–2019 years. The study provides an in-depth analysis of how to reduce CO2 emissions and the factors that contribute to their variation, which is crucial for both global and regional climate change policies. DA shows that, up to 2004, the activity effect and the population effect drove the emissions to increase; while, in more recent years, the activity effect was able to curb the emissions. Decoupling analysis show the prevalence of the expansive negative decoupling regime for the 1990–2004 and 2015–2019 periods, while several countries were in the strong decoupling phase over the central period (2005–2009). According to the results, further efforts to increase energy efficiency, political support for digitalization and decentralized energy systems, and setting up a unique emission trading system are recommended for air pollution reduction.